Pelatihan Pembuatan Media Pembelajaran (Tulis dan Mewarnai) untuk Guru TK Masjid Muslimin - Andrian, Andrian; Agustina, Ika; Lubis, Reniwati; Gunawan, Gunawan; Frianto, Herri Trisna (Jurnal Pengabdian Masyarakat, 2025)
This training on the development of writing and coloring learning media was conducted with the aim of enhancing the competencies of teachers at Masjid Muslimin Kindergarten in designing and creating creative, educational, and engaging teaching materials for early childhood learners. Writing and coloring media play a crucial role in developing fine motor skills, imagination, and cognitive abilities in young children. The training activities included an introduction to the concept of writing and coloring-based learning media, worksheet creation techniques, and the integration of Islamic values into learning materials. The training methods used were lectures, demonstrations, and hands-on practice, enabling participants to apply the outcomes in their teaching practices. The results of the program indicated an increase in creativity and teachers’ abilities to produce writing and coloring media that are appropriate for the characteristics of early childhood learners at Masjid Muslimin Kindergarten.